Розробка техніки рукопашного бою правоохоронців МВС України в системі спеціальної фізичної підготовки - Моргунов, О. А.; Morgunov, O. A.; ORCID: http://orcid.org/0000-0003-2259-3620; Ярещенко, О. А.; Yareschenko, O. A.; ORCID: http://orcid.org/0000-0002-2475-7572; Хацаюк, О. В.; Khatsaiuk, O. V.; ORCID: http://orcid.org/0000-0002-4166-9099; Белошенко, Ю. К.; Beloshenko, Yu. K. (Честь і закон. - 2018. - № 4 (67). - С. 67-74, 2018)
Подано результати проведеної апробації експериментальної техніки обеззброєння супротивника, озброєного холодною зброєю, під час навчально-тренувальних занять зі спеціальної фізичної підготовки. Викладено результати експериментальних досліджень, спрямованих на підвищення надійності захисту від холодної зброї. Під час досліджень використано відеокомпютерну систему експрес-аналізу техніки єдиноборств (ВКС “Katsumoto”). Відповідно до отриманих результатів розроблено експериментальні моделі техніки обеззброєння, які під час апробації значною мірою підвищили технічний арсенал курсантів – майбутніх правоохоронців МВС України.

The article presents the results of experimental studies aimed at increasing the reliability of protection against cold weapons. The pedagogical experiment was attended by cadets of junior high (military and police) school in the number of 40 people. The experiment lasted three months, during which 36 practical classes were held for 90 minutes each. On the eve of the pedagogical experiment, an analysis of scientific and methodological literature and Internet sources on service and applied martial arts was conducted. In accordance with the obtained theoretical components, a step-by-step plan for the development and improvement of experimental methods of hand-to-hand combat was developed. The evaluation of the technique of performing experimental techniques was carried out by expert estimation. In the course of researches, the video-computer system of express-analysis of technique of martial arts (VKS “Katsumoto”) was used, which greatly increased the technical readiness of the studied cadets of the experimental group. At all stages of the pedagogical experiment, video shooting was widely used, which allowed a qualitative correction of hand-to-hand fighting techniques. In accordance with the obtained results, experimental models of disarmament technology have been developed, which during the testing significantly improved the technical arsenal of cadets-law enforcement officers.

Представлены результаты проведенной апробации экспериментальной техники обезоруживания противника, вооруженного холодным оружием, во время учебно-тренировочных занятий по специальной физической подготовке. Изложены результаты экспериментальных исследований, направленных на повышение надежности защиты от холодного оружия. Во время исследований использовалась видеокомпьютерная система экспресс-анализа техники единоборств (ВКС “Katsumoto”). Согласно полученным результатам разработаны экспериментальные модели техники обезоруживания, которые во время апробации значительно повысили технический арсенал курсантов – будущих правоохранителей МВД Украины.
Development of the hand-to-hand fighting of law enforcement officers of the MIA of Ukraine in the system of special physical training
Разработка техники рукопашного боя правоохранителями МВД Украины в системе специальной физической подготовки
Моргунов, О. А. Розробка техніки рукопашного бою правоохоронців мвс україни в системі спеціальної фізичної підготовки / О. А. Моргунов, О. А. Ярещенко, О. В. Хацаюк, Ю. К. Белошенко // Честь і закон. - 2018. - № 4 (67). - С. 67-74.
Keywords: Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; спеціальна фізична підготовка; special physical training; специальная физическая подготовка; військовослужбовці; military personnel; военнослужащие; поліцейські; police officers; полицейские; спеціально-підготовчі вправи; special preparatory exercises; специально-подготовительные упражнения; технічна підготовка; technical training; техническая подготовка; техніка рукопашного бою; hand-to-hand combat technique; техника рукопашного боя; захист від загрози холодною зброєю; protection against the threat of cold weapons; защита от угрозы холодным оружием; обеззброєння супротивника